Identifikasi Jenis-Jenis Echinodermata Pada Ekosistem Lamun Pantai Pandaratan Kabupaten Tapanuli Tengah, Provinsi Sumatera Utara - Sri Wahyuni; Ipanna Enggar Susetya (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
This study aimed to identify types of Echinoderms and charactheristics of Echinoderms in Pandaratan Beach. This research was conducted from April to May 2018. The samples was taken from 3 stations with repeating 3 times in Pandaratan Beach Central Tapanuli Regency of North Sumatra Province. The results of the research was found as many as 1472 individuals consisting of 4 classes and 7 species. The type of Echinoderms results are Archaster typicus, Diadema setosum, Lagamun laganum, Holothuria atra, Holothuria leucospilota, Holothuria scabra and Ophiocoma erinaceus.Keywords: Identification, Echinoderms, Pandaratan Beach